2011
DOI: 10.1002/dev.20598
|View full text |Cite
|
Sign up to set email alerts
|

Attachment security and HPA axis reactivity to positive and challenging emotional situations in child–mother dyads in naturalistic settings

Abstract: This study investigated adrenocortical activity in response to different challenging and positive affect emotional contexts in child-mother dyads, as function of attachment security (children's secure base behaviors and mothers' attachment representations). Fifty-one children ranging in age from 18 to 26 months and their mothers participated in this study. Secure children showed significant increases in their cortisol levels after fear episodes and significant decreases, after positive affect ones. No signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
19
0
2
Order By: Relevance
“…Gunnar and colleagues were among the first to directly examine the relation of HPA functioning to assessments of attachment security in childhood [16], and this work was the catalyst for dozens of later studies, which clarified that insecure attachment in infants [17], school-age children [18] and adolescents [19] is associated with hyper- or hypo-responsiveness of the HPA system. Recent studies confirm the association of insecure attachment with both hyperactivated [20] and hypoactivated stress responses [21], and extend the earlier literature by clarifying the importance of the particular dyadic context of attachment (e.g. whether attachment is assessed with mother, father, or teacher) and the context of the type of stressor (e.g.…”
Section: Attachment and Hpa Regulationsupporting
confidence: 69%
“…Gunnar and colleagues were among the first to directly examine the relation of HPA functioning to assessments of attachment security in childhood [16], and this work was the catalyst for dozens of later studies, which clarified that insecure attachment in infants [17], school-age children [18] and adolescents [19] is associated with hyper- or hypo-responsiveness of the HPA system. Recent studies confirm the association of insecure attachment with both hyperactivated [20] and hypoactivated stress responses [21], and extend the earlier literature by clarifying the importance of the particular dyadic context of attachment (e.g. whether attachment is assessed with mother, father, or teacher) and the context of the type of stressor (e.g.…”
Section: Attachment and Hpa Regulationsupporting
confidence: 69%
“…Studies were included in this meta-analysis if they reported on the association between early attachment and (a) baseline physiological activity and/or (b) physiological reactivity to interpersonal stress. Studies reporting on physiological reactivity to noninterpersonal stressors (e.g., emotion-eliciting procedures designed to assess temperament, e.g., Paret, Bailey, Roche, Bureau, & Moran, 2015;Roque, Ver ıssimo, Oliveira, & Oliveira, 2012;Van Bakel & Riksen-Walraven, 2004) or during cognitive engagement tasks (Kidwell, 2001) were excluded from the current meta-analysis. As specified, the corpus of studies focused on physiological reactivity to interpersonal stress, and all but one study examined reactivity in response to separation-reunion procedures (e.g., SSP; Ainsworth et al, 1978).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…High postpartum maternal cortisol levels measured at rest have been associated with disrupted maternal behaviours, including decreases in infant‐directed maternal gaze, positive affect and vocalisation, and affectionate touch, as well as synchrony and positive engagement with infants . Increased maternal resting cortisol has also been associated with insecure attachment relationship between mother and infant, as well as decreased maternal sensitivity to infant cues . In addition, heightened maternal cortisol reactivity has also been linked to compromised maternal behaviour, such as increased harsh, intrusive parenting and decreased synchrony during mother‐infant interactions .…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 99%
“…67 These findings are generally in support of an association between elevated maternal cortisol and increased stress behaviour in the infant, although infant's stress behaviours and HPA responses can be dissociated depending on age 107 and attachment security. 98 For the mother who is already vulnerable to heightened stress, such a pattern of stress dysregulation in the infant may serve as an additional stressor in her postpartum adaptation, which may contribute to an intergenerational cycle of stress dysregulation.…”
Section: Hpa Axis Hormonesmentioning
confidence: 99%